Bilateral ovarian serous cystadenocarcinoma in a teenager: a case report. (2017)
Background: Genital Chlamydial trachomatis infection, though often asymptomatic, is an established indirect causative agent of female infertility via its activities on the tubal physiology. Many risk factors are postulated for its acquisition and the main thrust of this study was to establish the organisms’ correlates among infertile women attending gynaecologic clinic in Ibadan. Methods: A systematic sampling technique was used on each selected day to recruit women who met the inclusion criteria into the study using a sampling frame of 2. Interviewer-administered questionnaires were used to obtain attributes considered as risk factors for acquiring genital Chlamydia trachomatis infection from 150 consenting infertile women between January and November 2015. These attributes included sexual history, social status, alcohol intake and past history of sexually transmitted infections (STIs). Blood samples and endocervical swabs were subsequently taken for detection of C. trachomatis infection using polymerase chain reaction (PCR). Data analysis was done using SPSS version 20.0. Results: The mean age of the respondents was 34.1±5.6 years and 7.30% were positive for C. trachomatis. Chlamydia trachomatis infection was significantly associated with past history of gonorrhoea, history of multiple sexual partners, husband that has other sexual partners and lifetime sexual partners greater than one. Conclusions: The prevalence of asymptomatic C. trachomatis among infertile women indicated the pathogen as a potential aetiologic agent of female infertility and supported the asymptomatic nature of the infection. The risk factors found to be associated with the organisms’ infection lend out further support to the sexual transmissibility of C. trachomatis.